2021
DOI: 10.1016/j.psj.2020.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Day-old chicken quality and performance of broiler chickens from 3 different hatching systems

Abstract: In on-farm hatching systems, eggs are transported at d 18 of incubation to the broiler farm, where chickens have immediate access to feed and water after hatching. In hatchery-fed systems, newly hatched chickens have immediate access to feed and water in the hatchery and are transported to the farm thereafter. Conventionally hatched chickens can remain without access to feed and water up to 72 h after hatching until placement on the farm. The current study compared day-old chicken quality, performance, and sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 40 publications
10
45
1
Order By: Relevance
“…(2019) found no difference in hatchability when using the standard method for calculation for both treatments. The present study and Souza da Silva et al. (2021) found a similar result when second grade chicks were included as hatched chicks.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(2019) found no difference in hatchability when using the standard method for calculation for both treatments. The present study and Souza da Silva et al. (2021) found a similar result when second grade chicks were included as hatched chicks.…”
Section: Discussionsupporting
confidence: 87%
“…In line with other studies, a reduced chick quality was found for chicks hatched OF ( van de Ven et al., 2012 ; de Jong et al., 2019 , 2020 ). Souza da Silva et al. (2021) reported conflicting results as they found that OF hatched chicks had worse navel and hocks, but were longer, the latter being considered a positive chick quality indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches to early feeding, including in ovo and hatcher feeding, have been investigated with varying degrees of success, as reviewed by multiple authors ( Noy and Sklan, 1999 ; Noy and Uni, 2010 ; Willemsen et al, 2010 ). Commercially, the ability to provide early nutrition to chicks is dictated by the particular hatching system being utilized, and both hatcher-feeding and on-farm hatching with immediate feed and water access may enhance broiler performance ( van de Ven et al, 2011 ; Souza da Silva et al, 2021 ). One method of early feeding is providing nutrients immediately posthatch in the hatching baskets or during transportation from the hatchery to the farm.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that immediate access to feed improves growth and development during the first week posthatch, though compensatory growth of fasted and early hatching chicks often diminishes these early benefits ( Kidd et al, 2007 ; Lamot et al, 2014 ; Deines et al, 2021 ). Recently, Souza da Silva et al (2021) demonstrated potential for sustained benefits in BW, but not FCR, to 39 d posthatch when chicks were fed in the hatcher or hatched on farm, highlighting the need for additional research to better understand broiler responses to hatcher feeding.…”
Section: Introductionmentioning
confidence: 99%